PENGANGKATAN ANAK TANPA MELALUI PROSEDUR HUKUM YANG BERLAKU: Adoption of a Child Without Following the Applicable Legal Procedures - Uray Naya Ramadhani; Setyaningsih (Faculty of Law, Universitas Trisakti, 2026)
Child Adoption is a legal act intended to ensure the best interests of the child. In practice, adoptions carried out without compliance with applicable legal procedures are still found. The legal problem issue examined in this research concerns the implications of regulations governing adoption conducted without fulfilling legal procedures. This study employs normative legal research using a statutory approach, emphasizing principles of family law, particularly in the field of adoption. It is descriptive and analytical, utilizing secondary data analyzed qualitatively and through deductive reasoning. The findings result and conclusion show that adoption conducted without the prescribed legal procedures, particularly in the absence of a court determination, constitutes an unlawful act. Consequently, the legal status of the adopted child is not recognized, and no civil legal relationship arises between the adopted child and the adoptive parents. This condition results in the non-fulfillment of the child’s rights, including legal protection, certainty of identity, and welfare guarantees. Therefore, adoption must be carried out in accordance with applicable legal provisions to ensure legal certainty and protection for the child